Economic Process Evaluation and Environmental Life-Cycle Assessment of Bio-Aromatics Production - Krömer, Jens O.; Ferreira, Rafael G.; Petrides, Demetri; Kohlheb, Norbert (Frontiers in Bioengineering and Biotechnology, 2020)
The bio-based production of aromatics is experiencing a renaissance with systems and synthetic biology approaches promising to deliver bio-catalysts that will reach yields, rates and titers comparable to already existing bulk bio-processes for the production of amino acids for instance. However, aromatic building blocks derived from petrochemical routes have a huge economic advantage, they are cheap, very cheap in fact. In this article, we are trying to shed light on an important aspect of biocatalyst development that is frequently overlooked when working on strain development: economic and environmental impact of the production process. We estimate the production cost and environmental impact of a microbial fermentation process depending on culture pH, carbon source and process scale. As a model molecule we use 4-hydroxy benzoic acid (pHBA), but the results are readily transferrable to other shikimate derived aromatics with similar carbon yields and production rates.